LIVE Course for free

Rated by 1 million+ students
Get app now
0 votes
27 views
in Determinants by (91.8k points)
closed by
Solve : `(3x +4)/(7) - (x +5)/(14) = (x)/(28) + (x +1)/(14)`
The following steps are involved in solving the above problem. Arrange them in sequential order
(A) `5x + 3 = (3x + 2)/(2) rArr 10 x + 6 = 3x + 2`
(B) `rArr 7x = -4`
(C) Given `(3x + 4)/(7) - (x + 5)/(14) = (x)/(28) + (x +1)/(14)`
`rArr (6x + 8 -x -5)/(14) = (x + 2x + 2)/(28)`
(D) `rArr x = -(4)/(7)`

1 Answer

0 votes
by (91.1k points)
selected by
 
Best answer
Correct Answer - x=-2
`(3x xx 4) - 7 xx (-2) = 32-42 rArr 12x +14 =-10 rArr 12x = -24 rArr x = -2`

Welcome to Sarthaks eConnect: A unique platform where students can interact with teachers/experts/students to get solutions to their queries. Students (upto class 10+2) preparing for All Government Exams, CBSE Board Exam, ICSE Board Exam, State Board Exam, JEE (Mains+Advance) and NEET can ask questions from any subject and get quick answers by subject teachers/ experts/mentors/students.

...